Laboratory Diagnosis of Acquired Hemophilia A: Limitations, Consequences, and Challenges - Tiede, Andreas; Werwitzke, Sonja; Scharf, Rüdiger E. (Seminars in Thrombosis and Hemostasis, 2014)
Acquired hemophilia A (AHA) should be suspected in patients with a new onset of bleeding and an isolated prolongation of activated partial thromboplastin time. About 10% of patients do not bleed at the time of diagnosis, but are at risk of future bleeding, particularly during interventions or surgery. Diagnosis of AHA is confirmed by demonstrating markedly reduced factor VIII activity (FVIII:C) and neutralizing anti-FVIII antibodies, so-called inhibitors. Several limitations and pitfalls exist with the assays used to diagnose AHA. Interference can result from anticoagulants or lupus anticoagulant. The Bethesda assay used to measure inhibitor potency assumes a log–linear relationship between inhibitor concentration and effect on residual FVIII:C activity to allow exact quantification. However, this relationship is not present for the type 2 inhibitors typically seen in AHA. Therefore, this assay only provides a rough estimate of inhibitor potency. These limitations can explain, in part, why laboratory data, such as inhibitor potency, failed to predict bleeding or response to treatment in AHA. This article reviews the diagnostic approach to AHA, discusses assay-specific limitations and addresses some of the challenges for future research.
Keywords: acquired hemophilia; factor VIII; inhibitor; autoantibody